NÃO ESTÃO NA ESCOLA?: Um estudo sobre a evasão na Educação de Jovens e Adultos nos Anos Iniciais na Rede Municipal de Pelotas - Garcia, Rogeria Aparecida (2013)
The research presents a study about the evasion of young people and adults from classes in the early years of EJA (young and Adults education). The chose to search this phenomenon is the result of several studies processes in the researcher groups MovSE (social movements, public school and Popular Education) e FePráxiS (philosophy, education and Social praxis) of Education College, Federal University of Pelotas. In the process there was the identification of the theme relevance in Brazilian educational scene and the education recognition of young and adult as a problem that marks the history of education in Brazil and in Pelotas with regard to the schooled teaching. The theoretical and methodological benchmark, in a qualitative base, aligns the dialectics Materialist Historical prospect. We opted for a case study accomplished in an outskirts school of Pelotas city. The data collection strategies were observations and interviews, in 2012, with the directive team (principal and pedagogical coordinator) and two teachers of early years classes in EJA. 24 students who left school in the 2009, 2010 and 2011 years, were also interviewed in their homes. For analysis, the systematization considered the average age, occupation / job, gender, ethnic and origin in relation to urban and rural areas. Among the dropout causes, the research concluded that macros social factors directly affect the basic subsistence conditions and life maintenance protrude to the micros social factor, relationship didactic-methodological: Brazilian schools are included in an excluder system that expels the young and adults from school, also because of the dropout, denying the right of access to knowledge historically produced by humanity.